Pelatihan Strategi Membaca Komprehensif untuk Meningkatkan Literasi Membaca Siswa Sekolah Dasar - Surismiati Surismiati; Tias Fadakosta; Ayu Wulandari; Kurnia Saputri (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Reading literacy is a fundamental competency that supports students' academic achievement and lifelong learning. However, the rapid advancement of digital technology has changed students' reading habits, while many elementary school students still experience difficulties in identifying main ideas, interpreting information, and comprehending both printed and digital texts. Initial observations at SD Muhammadiyah 16 Palembang also indicated that teachers required greater capacity to implement structured reading instruction. This community service program aimed to improve students' reading literacy and strengthen teachers' instructional competence through comprehensive reading strategy training. The program employed a participatory approach consisting of needs assessment, interactive training, guided practice, and continuous mentoring, emphasizing pre-reading, while-reading, and post-reading strategies integrated with printed and digital learning resources. The program resulted in improved student engagement, enhanced reading comprehension skills, and increased teacher competence in implementing comprehensive reading strategies. In addition, practical instructional guidelines were developed to support sustainable literacy practices at the school level. These findings demonstrate that comprehensive reading strategy training is an effective approach to strengthening reading literacy and fostering a sustainable literacy culture in elementary schools.